The Girlhood Project: Pivoting our Model with Girls During COVID-19. Issue 3 (1st December 2020) - Weiner, Cheryl; Van Demark, Kathryn; Doyle, Sarah; Martinez, Jocelyn; Walklet, Fia; Rutstein-Riley, Amy
Abstract: The Girlhood Project (TGP) is a community based, service-learning/research program that is part of the undergraduate course at Lesley University called "Girlhood, Identity and Girl Culture." TGP works with community partners to bring middle and high school girls to Lesley's campus for nine weeks as part of intergenerational girls' groups that are co-facilitated by Lesley students (also referred to as TGP students). TGP fosters the development of feminist leadership, critical consciousness, voice, and community action, and activism in all participants. In this article, we describe how we adapted TGP's model to a virtual and synchronous platform for students during COVID-19 and supported their learning competencies. We reflect critically on this experience by centering the voices and perspectives of girls, students, and professors.